Imaging pathology in archived cornea with Fuchs’ endothelial corneal dystrophy including tissue reprocessing for volume electron microscopy - Sayo Maeno; Philip N. Lewis; Robert D. Young; Yoshinori Oie; Kohji Nishida; Andrew J. Quantock (Scientific Reports)
Abstract Fuchs’ endothelial corneal dystrophy (FECD) is a common sight-threatening condition characterised by pathological changes in the posterior cornea. Here we report observations by light, transmission and volume scanning electron microscopy on changes in the endothelium and matrix associated with the characteristic deformations of Descemet’s membrane, termed guttae. Specimens were archived full-thickness human corneal tissue, removed during graft surgery, that had been fixed, stained and embedded by conventional processing methods for examination by transmission electron microscopy more than 40-years previously. Intact archived samples can be extremely valuable where, as with FECD, new cell-based methods of therapy now avoid excision of the full cornea thickness and any tissue excised is inferior for study. Volume electron microscopy, in particular serial block face scanning electron microscopy (SBF SEM), employing backscatter electron detection from resin-embedded specimens, has become an invaluable technique for 3D imaging of biological samples. However, archived specimens are normally considered unsuitable for imaging as conventional processing methods generate low backscatter electron yield. To overcome this for SBF SEM, we subjected epoxy resin-embedded specimens to de-plastination, then applied additional contrasting agents, uranyl acetate and lead acetate, prior to re-embedding. Selected regions of interest in the new resin blocks were examined in a scanning electron microscope equipped for SBF SEM and serial image datasets acquired. Enhanced contrast enabled 3D reconstruction of endothelium and guttae in Descemet’s membrane over large tissue volumes.